Effect of inotropic agents on oxygenation and cerebral perfusion in acute brain injury - Coppalini, Giacomo; Duvigneaud, Elie; Diosdado, Alberto; Migliorino, Ernesto; Schuind, Sophie; Creteur, Jacques; Taccone, Fabio Silvio; Gouvêa Bogossian, Elisa (Frontiers in Neurology, 2022)
Introduction Tissue hypoxia and insufficient energy delivery is one of the mechanisms behind the occurrence of several complications in acute brain injured patients. Several interventions can improve cerebral oxygenation; however, the effects of inotropic agents remain poorly characterized. Methods Retrospective analysis including patients suffering from acute brain injury and monitored with brain oxygen pressure (PbtO2) catheter, in whom inotropic agents were administered according to the decision of the treating physician's decision; PbtO2 values were collected before, 1 and 2 h after the initiation of therapy from the patient data monitoring system. PbtO2 “responders” were patients with a relative increase in PbtO2 from baseline values of at least 20%. Results A total of 35 patients were included in this study. Most of them (31/35, 89%) suffered from non-traumatic subarachnoid hemorrhage (SAH). Compared with baseline values [20 (14–24) mmHg], PbtO2 did not significantly increase over time [19 (15–25) mmHg at 1 h and 19 (17–25) mmHg at 2 h, respectively; p = 0.052]. A total of 12/35 (34%) patients were PbtO2 “responders,” in particular if low PbtO2 was observed at baseline. A PbtO2 of 17 mmHg at baseline had a sensibility of 84% and a specificity of 91% to predict a PbtO2 responder. A significant direct correlation between changes in PbtO2 and cardiac output [r = 0.496 (95% CI 0.122 to 0.746), p = 0.01; n = 25] and a significant negative correlation between changes in PbtO2 and cerebral perfusion pressure [r = −0.389 (95% CI −0.681 to −0.010), p = 0.05] were observed. Conclusions In this study, inotropic administration significantly increased brain oxygenation in one third of brain injured patients, especially when tissue hypoxia was present at baseline. Future studies should highlight the role of inotropic agents in the management of tissue hypoxia in this setting.